1994
DOI: 10.1111/j.1749-6632.1994.tb44273.x
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Stress Protects Female Mice against Bacterial Infection of the Bladder by Eliciting Uroepithelial Shedding

Abstract: We have previously shown (M. Aronson, 0. Medalia, D. Amichay, and 0. Nativ, Infect. Immun. 56:1615-1617, 1988) that shedding of viable uroepithelial cells (elicited by invading microorganisms) constitutes an antimicrobial defense mechanism. The present study deals with two different stress-involving procedures, in which increased uroepithelial shedding rendered female mice resistant to vesical infection. Moderate stress was induced in female mice by exposing the animals either to constant illumination for 96 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 4 publications
4
33
0
Order By: Relevance
“…The prevalence of urinary frequency increases by 33[en]50%, the prevalence of urgency doubles, and the prevalence of nocturia increases by 25% in those that report experiencing abuse compared to those who do not. Any relationship producing an odds ratio (OR) indicating at least a 2-fold difference (OR ≥ 2.0 or ≤ 0.5) is unlikely to be due to chance.…”
Section: Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of urinary frequency increases by 33[en]50%, the prevalence of urgency doubles, and the prevalence of nocturia increases by 25% in those that report experiencing abuse compared to those who do not. Any relationship producing an odds ratio (OR) indicating at least a 2-fold difference (OR ≥ 2.0 or ≤ 0.5) is unlikely to be due to chance.…”
Section: Strengthmentioning
confidence: 99%
“…Stress induced by water immersion, cold, or restraint alters bladder histology and pharmacology [17,18,33,34]. Stress increases muscarinic-induced contractile responses in the bladder [19].…”
Section: Biologic Plausibilitymentioning
confidence: 99%
“…In con-FIG. 8.-Urinary bladder epithelium from a rat fed 7.5% sodium saccharin that was frequently handled (Group 4) showing prominent pleomorphism and hyperplasia. X 1,550. trast, the bladder of only 1 rat in the control group that was frequently handled (Group 3) was classified as a 1 or a 2, and 5 of the rats in this group had appreciable changes (Class 5), including diffuse superficial necrosis and piling up of small, round cells indicative of mild hyperplastic changes (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The turnover of urothelium is 40 weeks in the normal adult bladder; 10 however, desquamation of urothelial cells can be induced by injection of bacterial endotoxins into the bladder, 11 depletion of calcium from urothelial cells, 12 application of stress hormones to the bladder wall 13 or by reduction of blood flow to the bladder. 14 Lepilahti et al 15 and others 14,16 suggested that any condition that produces urinary retention resulting in Child is 1-12 years of age and adult is 44-46 years of age Figure 1 Normal bladder epithelium and lamina propria from a child with vesicoureteral reflux (H&E, Â 200) Figure 2 Immunoperoxidase staining exhibits a strong and specific reactivity with anti-uroplakin antibody in a uniform pattern restricted to the apical surface of the umbrella cells ( Â 200) overdistention of the bladder may decrease blood flow to the bladder wall and result in a damaged urothelium.…”
Section: Discussionmentioning
confidence: 99%